ANALISIS WACANA KRITISTAGAR FOODPORN DAN HALALFOOD PADA INSTAGRAM - Almyra Diah Pangestu; Aceng Rahmat, Novi Anoegrajekti (Prosiding Seminar Nasional Indonesia, 2024)
This study aims to analyze the meaning behind the discourse of foodporn hashtags and halalfood hashtags in their use in the variety of social media language on the Instagram application. This research methodology is descriptive qualitative with content analysis. The data used in this method are uploads of foodporn hashtags and halalfood hashtags on Instagram from 32 Instagram accounts then analyzed using critical discourse analysis theory by Fairclough. The hashtags #halalfood and #foodporn which are part of a whole discourse related to food have different meanings based on textual analysis, analysis of discourse practices, and analysis of sociocultural practices. The hashtags #halalfood and #foodporn have different ideological meanings. The hashtag #halalfood is the language used by discourse makers to communicate with readers who practice Islamic principles, while the hashtag #foodporn is used by discourse makers to communicate with readers who have a lifestyle of worldly pleasure. The hashtags #halalfood and #foodporn have the same meaning in trying to influence readers to enjoy food and tools used in the economic field.